2011
DOI: 10.1111/j.1747-0285.2011.01207.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Stability of Peptidomimetics: N‐Methyl and Aza Heptapeptide Analogs of a PKB/Akt Inhibitor

Abstract: Linear peptides suffer from poor pharmacokinetic and pharmacodynamic properties. Peptidomimetics are designed to overcome these pharmacological drawbacks while maintaining the biological effects of the parent peptides. Aza-peptides, in which an alpha carbon is replaced with nitrogen, are promising peptidomimetic analogs; however, little is known about the stability of these analogs toward enzymatic degradation. We performed systematic aza and N-methyl scans of a PKB/Akt inhibitor, PTR6154. We evaluated the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Because our SAR study did not yield new dnCSPs with higher potencies or pan‐group reactivity, we evaluated the therapeutic potential of the previously reported lead ComD1 and ComD2 dnCSPs, CSP1‐E1A and CSP2‐E1Ad10, respectively. First, we assessed the metabolic stability of CSP1‐E1A and CSP2‐E1Ad10 by using an in vitro trypsin/chymotrypsin stability assay . The stability of the two dnCSPs was compared against CSP1 and CSP2.…”
Section: Resultsmentioning
confidence: 99%
“…Because our SAR study did not yield new dnCSPs with higher potencies or pan‐group reactivity, we evaluated the therapeutic potential of the previously reported lead ComD1 and ComD2 dnCSPs, CSP1‐E1A and CSP2‐E1Ad10, respectively. First, we assessed the metabolic stability of CSP1‐E1A and CSP2‐E1Ad10 by using an in vitro trypsin/chymotrypsin stability assay . The stability of the two dnCSPs was compared against CSP1 and CSP2.…”
Section: Resultsmentioning
confidence: 99%
“…Azapeptides are peptide mimics that contain one or multiple semicarbazides, in which nitrogen replaces an amino acid residue α‐carbon . Aza‐residues can favor β‐turn geometry and enhance peptide metabolic stability . Linear azapeptides have been established as drugs; however, their macrocycle counterparts have only begun to be explored .…”
Section: Methodsmentioning
confidence: 99%
“…With the overall conformational change that can occur with N-methylated peptides, and the change in H-bonding capacity and steric features, N-methylation often leads to a decreased affinity of the peptide for the active site of proteases and therefore increased metabolic stability. It has also been found that N-methylation of an amide bond adjacent to the cleavage site can confer a greater resistance against enzymatic degradation than N-methylation of the amide bond at the cleavage site itself [89]. This behavior may result from N-methylation making the cis conformation readily accessible and then becoming the preferred conformation of the peptide in vivo.…”
Section: N-methylationmentioning
confidence: 99%